Exploration of Malaysian school-children's food preferences: what do we know?. (27th September 2022) - Yang, Wai Yew; Ong, Shu Hwa; De Lee, Yi; Yen, Pei Ling; Lim, Kah Yen; Naumoskvi, Nenad; Jani, Rati
Abstract: Background: Feeding practices exert a definite influence over children's experiences. This article aims to explore parental feeding practices and investigate the prediction domain of food preference from parent–child perspectives. Methods: Two individual studies were conducted on Malay families with children aged 7–12 years. In Study 1, mothers ( n  = 17) participated in semi-structured focus group interviews on their knowledge of foods and feeding practices. In Study 2, parent–child pairs ( n  = 14) answered a 36-item, 5-point Likert scale Food Preference Questionnaire followed by virtual structured qualitative interviews. The interviews were digitally recorded, transcribed verbatim, back-translated and analysed according to the framework analysis technique. Results: In Study 1, mothers perceived vegetables, chicken, fish and plain water as healthy foods and drinks while discretionary options were snacks, fast foods and carbonated drinks. The mothers defined healthy foods as foods handled safely with health benefits. They used 'healthy' cooking methods to prepare preferred foods and overtly controlled the child's access to discretionary food. In Study 2, the food groups reported by parent–child pair's report were consistent for the most preferred foods [snacks, median (interquartile range), parent: 4.5 (1.0) vs. child: 4.5 (0.0), p  > 0.05] and least preferred food [legumes, parent: 2.0 (1.0) vs. child: 2.0 (1.0), p  > 0.05]. Parents emphasized taste as the key determinant of food preference. Conclusion: These studies were the first to qualitatively explore parents' perceptions of foods affecting their feeding practices among the Malaysian community to highlight the cultural contribution. Key insights into children's food intake and factors influencing their food preferences were identified.